MODL-20. Metabolic rewiring support the onset of chemotherapy resistance in medulloblastoma. (3rd June 2022) - Bortolozzi, Roberta; Mariotto, Elena; Rampazzo, Elena; Manfreda, Lorenzo; Marchioro, Chiara; Rruga, Fatlum; Persano, Luca; Viola, Giampietro
Abstract: Medulloblastoma (MB) is the deadliest brain tumor of childhood, intrinsically characterized by fast growth, high invasiveness, and resistance to treatments. With the aim to deepen the molecular basis of MB aggressiveness and recurrence, we established an in vitro model of MB resistance to chemotherapy, in which, a weekly exposure to a cocktail of chemotherapeutics commonly used in MB treatment (Vincristine, Etoposide, Cisplatin, Cyclophosphamide – VECC) induces the selection of cells that progressively acquire resistance to subsequent VECC treatments. Preliminary data on our model of MB resistance show that resistant cells induce the activation of the two main regulator of pentose phosphate pathway TKT and G6PD via the activation of Nrf2 transcriptional activity. Moreover, resistant cells show an increase in hypoxia inducible factor-1α (HIF-1α) together with an augmented expression of glycolytic enzymes HK1, PFKB-3, PDK1 and LDHA and increased glycolytic capacity. Interestingly, enrichment analysis on label free mass spectrometry data reveal that the most significant terms deriving from the upregulated proteins, that characterized resistant cells, were related to metabolic processes such as "carbon metabolism", "fatty acid beta oxidation", "tricarboxylic acid cycle" and "carboxylic acid catabolic processes".Consistently with recent studies that highlight the relevance of metabolic plasticity of cancer cells in chemotherapy adaptation, our data suggest a metabolic uncoupling in which MB resistant cells, through the alteration of peculiar metabolic processes, may satisfy their altered energetic demands through alternative metabolic pathways. In this way, the generation of a new balance of intracellular metabolites finally provide increased resistance to external insults (i.e., chemotherapeutics) and a greater ability of detoxifying the intracellular compartments.